2019
DOI: 10.3390/ijerph16050806
|View full text |Cite
|
Sign up to set email alerts
|

The UNICEF/Washington Group Child Functioning Module—Accuracy, Inter-Rater Reliability and Cut-Off Level for Disability Disaggregation of Fiji’s Education Management Information System

Abstract: This paper explores the validity (sensitivity and specificity) of different cut-off levels of the UNICEF/Washington Group Child Functioning Module (CFM) and the inter-rater reliability between teachers and parents as proxy respondents, for disaggregating Fiji’s education management information system (EMIS) by disability. The method used was a cross-sectional diagnostic accuracy study comparing CFM items to standard clinical assessments for 472 primary school aged students in Fiji. Whilst previous domain-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 45 publications
2
25
1
1
Order By: Relevance
“…The items on seeing, hearing, remembering things, controlling behavior, and getting friends could be interpreted to have had large agreement when the first level cut-off (at least some difficulties) was administered. These results partly contrast with the earlier evidence from the draft reliability tests of the CFM, whereby the levels agreements between parents and teachers were poor when reporting children who have at least some difficulty in getting friends [ 35 ]. Further evidence is needed that can be explained through triangulating the data from three main sources, the pupil, parents, and teacher before conclusions about these differing items can be made.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…The items on seeing, hearing, remembering things, controlling behavior, and getting friends could be interpreted to have had large agreement when the first level cut-off (at least some difficulties) was administered. These results partly contrast with the earlier evidence from the draft reliability tests of the CFM, whereby the levels agreements between parents and teachers were poor when reporting children who have at least some difficulty in getting friends [ 35 ]. Further evidence is needed that can be explained through triangulating the data from three main sources, the pupil, parents, and teacher before conclusions about these differing items can be made.…”
Section: Discussioncontrasting
confidence: 94%
“…However, the level of agreement on difficulties with self-care, concentrating on things the child enjoys, and having changes to the routine were only fair. Similar problems with the item on difficulties with self-care were reported in an inter-rater reliability study between parents and teachers, which found poor agreement [ 35 ]. This would suggest that these items may have different meanings at different times of survey completion, and may need to be interpreted with caution [ 21 ].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…For the purpose of this study, a child was considered to be experiencing disability at the level of ‘some difficulty’ with carrying out functional activities. 18 The tool has shown good diagnostic accuracy 19 in international research, and studies suggest using the cut off ‘some difficulty’ to identify children at risk of disability and then refer to a medical practitioner for an objective assessment. 18 , 19 …”
Section: Methodsmentioning
confidence: 99%